Epidemiological and clinical aspects of syphilis incidence in the Russian Federation and the Republic of Uzbekistan: comparative analysis - Margarita R. Rakhmatulina; Delya F. Porsokhonova; Elena Yu. Novoselova; Avaz Sh. Inoyatov (Vestnik Dermatologii i Venerologii)
The Soviet model of healthcare was characterized by the centralization of state medicine, which made it possible to effectively deal with mass epidemics, including STIs. After the collapse of the USSR, the dermatovenereological services of the Russian Federation and the Republic of Uzbekistan actively developed and improved, developing new effective methods of treatment and prevention of skin diseases and STIs and introducing them into healthcare practice, which ensured the maintenance of epidemiological well-being. The article presents the results of a retrospective comparative study of syphilis incidence rates in two countries, including an analysis of the earliest, most epidemiologically dangerous clinical forms. It was found that starting in 2019, the incidence of early syphilis in the Republic of Uzbekistan began to exceed the same indicator in the Russian Federation, while previously this indicator was higher in Russia. An analysis of syphilis cases in various age and gender populations by clinical forms of the disease demonstrated an increase in late and unspecified forms in Russia among the male population over the age of 40, while in Uzbekistan there was an increase in the number of cases of early latent syphilis among the same age group. As a result of the study of regulatory documents regulating algorithms and principles of management of patients with syphilis, differences in laboratory diagnostic algorithms and treatment regimens were revealed, namely lower dosages of drugs and shorter treatment courses for patients with syphilis in the Republic of Uzbekistan compared with those in the Russian Federation.